Les fonctions alimentaires de l’agriculture urbaine au Nord et au Sud - Diversité et convergences - Christine Aubry (Bulletin de l’Association de Géographes Français)
Today, urban agricultures both in the Global North and Global South emphasize its food productionfunction, which is proclaimed as a guarantee of food security, as a cushion in time of economic crises, and even en expression of regained autonomy vis-à-vis the power of the globalized agri-food system. This paper aims at exploring the specificities and convergences of agriculture in different contexts. It presents a multiple criteria reflection on farms active in urban agriculture (operating system, cropping system, location). Examples from Madagascar (Antananarivo) and Ile-de-France show the differences and similarities in actions.